The European Commission: Space and the Arctic - European Commission, -
Accompanying the document: Joint communication: Developing a European Union Policy towards the Arctic Region: progress since 2008 and next steps (http://library.arcticportal.org/1698/). The remoteness, low population density, marked seasonal variability and harsh meteorological conditions in the Arctic mean that Earth-orbiting satellites are essential tools for communication, navigation and observation in the region. With the entry into force of the “Lisbon Treaty”, article 189 of the Treaty on the Functioning of the European Union confers to the European Union a shared space competence which it pursues alongside that of the Member States. It is the basis for the definition of a EU Space policy of which the two flagships are Galileo, the European GNSS, and GMES, the European Earth monitoring programme. Space research and developments activities are funded under the space theme of the Seventh Framework Programme for research.